1984
DOI: 10.2134/jeq1984.00472425001300010014x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Four Terrestrial Herbicides on the Productivity of Artificial Stream Algal Communities

Abstract: Artificial streams containing algal communities derived from a spring and an agriculturally impacted stream were used to assess the effect of 0.1, 1, and 10 mg kg−1 atrazine [2‐chloro‐4‐(ethylamino)‐6‐(isopropylamino)‐s‐triazine], trifluralin (α,α,α‐trifluoro‐2,6‐dinitro‐N,N‐dipropyl‐p‐toluidine), MSMA (monosodium methanearsonate), and paraquat (1,1′‐dimethyl‐4,4′‐bipyridylium cation) on the productivity (photosynthesis and respiration) of stream algae. The importance of induced resistance to the herbicides wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 0 publications
1
38
0
Order By: Relevance
“…As noted above, these sites are in general diatom dominated, particularly periphytic assemblages and both periphyton and phytoplankton during the spring, when atrazine concentrations are frequently elevated. Diatoms and cyanophyta have been shown to be less sensitive to atrazine than other algal groups, particularly compared to chlorophyta, which typically show the highest sensitivity to atrazine (Goldsborough and Robinson, 1986;Kosinski and Merkle, 1984;Guasch et al, 1997Guasch et al, , 1998Guasch et al, , 2007Dorigo et al, 2004;Guanzon et al, 1996;Tang et al, 1998;Brain et al, 2012aBrain et al, , 2012b. It could therefore be expected that diatomdominated communities such as those in this study would be less sensitive overall to atrazine.…”
Section: Inertia Explained By Variable Group and By Individual Variablesmentioning
confidence: 68%
See 1 more Smart Citation
“…As noted above, these sites are in general diatom dominated, particularly periphytic assemblages and both periphyton and phytoplankton during the spring, when atrazine concentrations are frequently elevated. Diatoms and cyanophyta have been shown to be less sensitive to atrazine than other algal groups, particularly compared to chlorophyta, which typically show the highest sensitivity to atrazine (Goldsborough and Robinson, 1986;Kosinski and Merkle, 1984;Guasch et al, 1997Guasch et al, , 1998Guasch et al, , 2007Dorigo et al, 2004;Guanzon et al, 1996;Tang et al, 1998;Brain et al, 2012aBrain et al, , 2012b. It could therefore be expected that diatomdominated communities such as those in this study would be less sensitive overall to atrazine.…”
Section: Inertia Explained By Variable Group and By Individual Variablesmentioning
confidence: 68%
“…These studies have generally concluded that significant effects on primary producers typically only begin to occur with prolonged atrazine concentrations N30 μg/L and that subsequent to any disturbances algal populations recover (Gruessner and Watzin, 1996;Nyström et al, 2000;Baxter et al, 2011;Huber, 1993;Solomon et al, 1996;Giddings, 2012). However, mesocosm studies testing atrazine concentrations N 50 μg/L for extended periods have shown decreased activity, abundance, or diversity, or shifts in algal community structure (Kosinski and Merkle, 1984;Hamala and Kollig, 1985;Larsen et al, 1986;Krieger et al, 1988;Hamilton et al, 1988;Hamilton and Mitchell, 1997;Nyström et al, 2000;Guasch et al, 2007).…”
mentioning
confidence: 99%
“…Studies have examined the relative impacts of heavy metals (Williams & Mount, 1965;Dickman, 1974;Sigmon et al, 1977;Grolle & Kuiper, 1980), industrial effluent (Evans & Marcan, 1976;Moll & Keller, 1980) and pesticides (Anderson, 1981;Hodgson & Carter, 1982;Hodgson & Linda, 1984;Kosinski, 1984;Kosinski & Merckle, 1984) on dry weight and pigment concentration (Hodgson & Carter, 1982), physiological activity (Goldsborough & Robinson, 1983) and/or species composition (Kosinski, 1984;Leland & Carter, 1984) of artificial (Hodgson & Linda, 1984;Kosinski, 1984) or in situ (Goldsborough & Robinson, 1983) communities under a series of controlled treatments.…”
Section: Introductionmentioning
confidence: 99%
“…In the second case, artificial streams were used to conduct studies with atrazine under constant exposure (Kosinski 1984;Kosinski and Merkle 1984). The constant exposure of 10 mg/L atrazine produced a change in primary production and biovolume of algae (effect class 4, RT ¼ 0.08).…”
Section: Resultsmentioning
confidence: 99%